Mug20, a novel protein associated with linear elements in fission yeast meiosis - Estreicher, Anna (Springer-Verlag, 2012)
In the fission yeast, Schizosaccharomyces pombe, homologous chromosomes efficiently pair and recombine during meiotic prophase without forming a canonical synaptonemal complex (SC). Instead, it features simpler filamentous structures, the so-called linear elements (LinEs), which bear some resemblance to the axial/lateral element subunits of the SC. LinEs are required for wild-type recombination frequency. Here, we recognized Mug20, the product of a meiotically upregulated gene, as a LinE-associated protein. GFP-tagged Mug20 and anti-Mug20 antibody co-localized completely with Rec10, one of the major constituents of LinEs. In the absence of Mug20, LinEs failed to elongate beyond their initial state of nuclear dots. Foci of recombination protein Rad51 and genetic recombination were reduced. Since meiotic DNA double-strand breaks (DSBs), which initiate recombination, are induced at sites of preformed LinEs, we suggest that reduced recombination is a consequence of incomplete LinE extension. Therefore, we propose that Mug20 is required to extend LinEs from their sites of origin and thereby to increase DSB proficient regions on chromosomes.